Strategi Guru Ekstrakurikuler Dalam Meningkatkan Kemampuan Membaca Al-Quran Siswa Di Mts Riyadhus Sholihin - Tharisa Indah Syafitri; Nurhalima Tambunan; Sakban Lubis (Journal Of Dehasen Educational Review, 2026)
This study aims to analyze the strategies used by extracurricular teachers to improve students' ability to read the Qur'an at MTs Riyadush Sholihin and to identify the factors that support and hinder its implementation. This study uses a qualitative approach with a case study type. Data collection techniques were carried out through interviews, observations, and documentation. Research informants included the deputy head of the madrasah, tahfidz extracurricular teachers, and students participating in extracurricular activities. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the teachers' learning strategies were implemented through five stages, namely structured program planning, gradual implementation of tahsin and tahfidz learning, utilization of learning media, provision of motivation, and evaluation through reading tests and memorization tests. Supporting factors included teacher competence, school support, availability of facilities, and student interest. Meanwhile, the inhibiting factors were limited learning time, differences in students' initial abilities, and lack of practice in reading the Qur'an at home.